Moss gown. [Grade 5] - Hooks, William H.; Carrick, Donald (Boston : Houghton Mifflin, 1991)
After failing to flatter her father as much as her two evil sisters do, Candace is banished from his plantation and only after much time and meeting her Prince Charming, is her father able to appreciate her love.
Originally published: New York : Clarion Books, c1987 ; Reprinted in the Houghton Mifflin social studies trade book set, 1991.
Grade 5.
Large print.
Keywords: Fairy tales; Folklore -- United States